Determinants of fish consumption among older adults in the UK - Ekpenyong, Mandu Stephen; Ogunleye, Adetoro; Bakre, Aishat T. (Frontiers in Nutrition, 2025)
BackgroundEating fish regularly can lower the risks of heart disease, brain disorders, and overall mortality, especially in older adults. Even with these benefits, older people tend to eat less fish than younger people, and the reasons behind these eating habits are not well understood.AimThis study investigated the determinants of fish consumption among older adults in the UK. It focused on what they see as helpful or limiting factors and their beliefs about health.MethodsThe study used a qualitative approach with two focus group discussions involving 12 participants aged 60 and older, recruited from a local religious organisation in Wolverhampton, UK. Data was collected through semi-structured interviews based on available literature and expert advice. The transcripts were analysed using thematic analysis to find key themes. Rigour was maintained through reflection, the use of different moderators, and repeated coding.ResultsParticipants explained that their fish consumption is influenced by cultural traditions, religious beliefs, family habits, and personal tastes. Helpful factors included taste, health beliefs, and convenience. Barriers included cost, difficulty in preparation, and availability. Many participants acknowledged the physical and mental health benefits of eating fish, but they also expressed concerns about quality, authenticity, and misconceptions regarding frozen fish. These results show how dietary choices are affected by a mix of personal, social, and environmental factors.ConclusionAlthough older adults acknowledge the nutritional and health benefits of fish, practical barriers such as affordability, accessibility, and preparation challenges continue to limit intake. Addressing these barriers and promoting lifelong positive habits may support improved consumption and healthier ageing.